PENGARUH PERCEIVED EASE OF USE, ELECTRONIC WORD OF MOUTH DAN PERCEIVED SECURITY TERHADAP REPURCHASE INTENTION DI TIKTOK SHOP - Liesta Verawati (POLITEKNIK LP3I JAKARTA, 2023)
Online shopping is not only through e-commerce but, it can be done through social media. Tiktok aplication was originally just a platform for entertainment, currently can be used to make purchase transactions. This study aims to examine the effect of perceived ease of use, electronic word of mouth, and perceived security on repurchase intention in Tiktok Shop. A quantitative methodology was used. Data were collected from 197 respondents who have used Tiktok Shop for shopping and has been 18 years old. The data collection method used a questionnaire with Google Form. The data analysis technique used is PLS-SEM using Smartpls3.3 software to test measurement model and structural model and using SPSS version 26 to analyze respondent characteristics. The findings show that perceived ease of use, electronic word of mouth and perceived security have a positive and significant effect on repurchase intention at Tiktok Shop. Keywords: Perceived Ease of Use, Electronic Word of Mouth, Perceived Security, Repurchase Intention, Tiktok Shop.